Shari’ah supervision in the Yemeni Islamic banks: a qualitative survey - Ayedh A.M.; Echchabi A. (Emerald Group Publishing Ltd., 2024)
Purpose – The purpose of this study is mainly to comprehensively investigate the current practices of Islamic banks’ Shari’ah supervisory boards in the specific context of Yemen. Design/methodology/approach – The study uses a qualitative approach in the form of in-depth interviews of a number of Shari’ah scholars active within the Yemeni Islamic banks. Findings – The findings support the notion that Islamic banking still lacks regulations and standards, as the Yemeni Islamic banks are still following the minimum requirements and only apply the compulsory standards. Another key finding is that Islamic banks in Yemen apply similar principles in Fatwa issuance and Shari’ah compliance assurance, especially in referring to the different Madzhabs’ and scholars’ opinions because of the sensitivity of Yemeni community with regards to the Shari’ah compliance aspect. Finally, the procedure of Shari’ah review of the Islamic banks’ operations varied from the typical set of procedures to the loose ones in terms of the number of staff in the Shari’ah audit department and the application of a comprehensive survey or sampling to review the banks’ transactions. Originality/value – This study provides some valuable recommendations to further enhance the Shari’ah supervisory practices not only in Yemen but also in similar settings.